Transcranial Stimulation Improves Volume and Perceived Exertion but does not Change Power - Fortes, Leonardo de Sousa; Mazini-Filho, Mauro; Lima-Júnior, Daltonde; Machado, Daniel Gomes Silva; Albuquerque, Maicon Rodrigues; Fonseca, Fabiano de Souza; Ferreira, Maria Elisa Caputo (International Journal of Sports Medicine, 2021)
This study aimed to analyze the acute effect of anodal transcranial direct current stimulation (a-tDCS) over the primary motor cortex (M1) on the volume, perceived exertion, and neuromuscular performance measurements in trained and untrained adults. Twenty-four male adults (12 trained and 12 untrained) participated in this single-blind, randomized, and sham-controlled study. The participants performed three back squat repetitions using the 15RM load with maximal concentric velocity to assess neuromuscular performance before tDCS and 30-min after resistance exercise. Next, they were randomly assigned to a-tDCS over M1 or the sham condition. Participants performed ten sets of parallel back squat with 15RM load and repetitions sustained to momentary muscular failure. The total number of repetitions was higher (p<0.05) and perceived exertion was lower (p<0.05) after a-tDCS in both groups. Peak power, velocity, and force decreased in both groups after the RE session (p<0.05), but with a higher rate in untrained individuals (p<0.05). No significant effect was found for peak power, peak velocity, and peak force (p>0.05). This study suggests that using a-tDCS may improve the total volume of repetitions and perceived exertion in trained and untrained individuals.
Keywords: brain; strength training; neuroscience; rating of perceived exertion